Modelling Everyday Understandings of Mortality: A Qualitative Enquiry. (September 2022) - McEwan, Oona; McDermott, Mark R.; Hefferon, Kate
With few exceptions, much of the literature on mortality awareness (MA; the realization of one's own and other's mortality), though based on quantitative research, is focused on its negative effects and processes associated with fearing its occurrence. However, recent studies have demonstrated that MA is multifaceted and can be associated with positive processes and outcomes. Here, everyday understandings of MA were investigated using grounded theory. Ten participants engaged in one-off semistructured interviews about their everyday experiences of MA. Grounded theory analysis revealed four main themes: (a) Moments of MA, (b) Functionality of MA, (c) Coping strategies for MA, and (d) Inability to cope with MA . Each of these themes is composed of two to five subthemes. The results supported the notion that MA is experienced in a multidimensional manner, which appears to align with elements of the Multidimensional Mortality Awareness Measure and Model. Furthermore, positive and/or negative outcomes appeared to depend on the function attributed to MA by the individual. Therefore, the ability to attribute such function to MA appears to be important in our understanding of this key existential issue.